Digital Humanities and Ritual Space: A Reappraisal - Papantoniou Giorgos; Sarris Apostolos; Morris Christine E.; Vionis Athanasios K. (Open Archaeology, 2020)
In this editorial article for the Special Issue on Unlocking Sacred Landscapes: Digital Humanities and Ritual Space, we introduce the applicability of digital humanities to the study of ritual space. The Issue focuses on digital approaches both to ritual space and to artefacts relating to ritual practice and cult. The terms ritual and cult are used broadly to include sanctuaries, temples and churches, as well as the domestic and funerary spheres of life. We include contributions with a strong methodological focus on computational developments, digitisation processes and spatial analyses. Although the main focus of the Unlocking Sacred Landscapes (UnSaLa) Research Network is the Mediterranean region, we have also encouraged colleagues working in other areas of the world to contribute to this volume, with a view to stimulating wider methodological dialogues and comparative approaches. The chronological span ranges from prehistory to the recent past, and includes cultural heritage management.